Peningkatan Pemahaman tentang Pendidikan bagi Anak Berkebutuhan Khusus (ABK) “Studi Kasus di SLB Negeri 1 Jayapura” - Yuliana; Albertina Nasri Lobo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This service activity aims to provide awareness or increase understanding for teachers in the SLB Negeri 1 Jayapura environment about the importance of education for children with special needs. The method used in this service uses qualitative descriptive research. The results of this research show that the implementation of education in Special Schools does not always run smoothly. There are various problems, both internal and external, as happened at SLB Negeri 1 Jayapura. Seeing situations like this, researchers provide solutions in the form of counseling and assistance. Schools as educational institutions in society greatly determine the dynamics of students' personal development as learners. The teachers as class managers have made such efforts in designing learning and providing encouragement. Teachers become innovators and encouragers. The existence of schools is not only important for normal children, but is also useful for children with special needs (ABK) who have limitations and deficiencies when it comes to interacting with other people. In reality, there are sociocultural obstacles, as happened at SLB Negeri 1 Jayapura. The output achieved through this PKM is increasing the knowledge of teachers in partner schools to improve professionalism and quality of learning through better strategies and teacher roles.